Recommendation the Renewal of Environmental Criminal Law System of Premium Toward Remedium Ultimium Remedium - Karmilia, Rise (International Journal of Engineering and Technology, 2018)
The establishment of law No. 32 of the year 2009 on the management of environmental protection to provide protection for the rights of each person. The authority of the criminal judge has been limited by the enactment of the substance of legislation no. 32 Year 2009 basic enforcement provisions particularly about ultimum remedium. Environmental pollution cases such as the case of the B3 waste imported by PT Asia Pacifik Eco sustainable and mining company PT Freeport in Indonesia since the year 1967 is an example of environmental crime which has led to a permanent change. This study examines whether or not the validity period is still decent basic ultimum remedium. This research is the normative or legal research libraries and analyzed in qualitative descriptive basis.  The results obtained.
Keywords: Environment; Ultimium Remedium; the powers of the judge